Special Issue: Generative Models in Artificial Intelligence and Their Applications - Castelli, Mauro (2022)
Castelli, M. (Guest ed.), & Manzoni, L. (Guest ed.) (2022). Special Issue: Generative Models in Artificial Intelligence and Their Applications. Applied Sciences (Switzerland), 12(9), [4127]. https://doi.org/10.3390/app12094127